Prevalence of diarrheal diseases and associated factors among under-five children in Dale District, Sidama zone, Southern Ethiopia: a cross-sectional study - Behailu Melese; Wondimagegn Paulos; Feleke Hailemichael Astawesegn; Temesgen Bati Gelgelu (BMC, 2019)
Abstract Background Globally childhood diarrhoeal diseases continue to be the second leading cause of death, while in Ethiopia it kills half-million under-five children each year. Sanitation, unsafe water and personal hygiene are responsible for 90% of the occurrence. Thus, this study aimed to assess the prevalence and associated factors of diarrheal diseases among under-five children in Dale District, Sidama Zone, Southern Ethiopia. Methods A community-based cross-sectional study was conducted. A face to face interview using a structured questionnaire and observation checklist was used. A total of 546 households with at least one under-five children were selected using simple random sampling techniques. The data entry and cleaning were performed using Epidemiological information software (EPI Info) 3.5.1 and then exported to Statistical Package for Social Science (SPSS) version 16.0 for analysis. Frequencies and proportions were computed as descriptive analysis. Initially using bivariate analysis a crude association between the independent and dependent variables was investigated. Then, those variables with p-value ≤0.25 were included in multivariable analysis to determine the predictor variables for the outcome variables. Finally, further analyses were carried out using multivariable analysis at a significance level of p-value ≤0.05. Results A total of 537 children under the age of 5 years were included. The 2 weeks prevalence of diarrhea among children under the age of 5 years was 13.6, 95% CI (10.7, 16.5%). Educational level [AOR: 3.97, 95% CI (1.60, 8.916)], age of indexed child [AOR: 12.18, 95% CI (1.78, 83.30)], nutritional status [AOR: 6.41, 95% CI (2.47, 16.77.)], hand washing method [AOR, 3.10, 95% CI (1.10, 8.67)], hand washing after latrine [AOR: 2.73, 95% CI (1.05, 6.56)], refuse disposal method [AOR, 3.23, 95% CI (1.37, 7.60)] and housing floor material [AOR: 3.22, 95% CI (1.16, 8.91] were significantly associated with the occurrence of childhood diarrheal diseases. Conclusion Childhood diarrhea remains the commonest health problem in the study area. The findings have important policy implications for childhood diarrhoeal disease intervention programs. Thus, activities focusing on proper handwashing techniques at all appropriate times, proper refuse disposal, improving nutrition and better childcare also highly recommended.